ANTIMICROBIAL ACTIVITY OF STREPTOMYCES VARIABILIS STRAIN-VITUMVB03 ISOLATED FROM KANYAKUMARI MARINE SEDIMENTS - M, Shubha; B, Ushashi; S, Veena; Kv, Bhaskara Rao (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was focused on an evaluation of antimicrobial activity of actinobacterial isolated from Kanyakumari marine sediments. Methods: This study includes sample collection from Kanyakumari beach, followed by isolation of marine actinobacteria, screening for antibacterial activity and antifungal activity. Finally, the most active isolate was identified using 16S rRNA sequencing.Â Results: Marine actinobacteria are one of the leading microbes of the ocean known for producing excellent secondary metabolites and having a broad spectrum of anti-microbial activity, hence they are very important from an industrial point of view. The marine sediment sample used was collected from Kanyakumari beach, in the month of July, falling in the latitudinal range of 8.5074Â°N and in the longitude of 76.9730Â°E. A total of 8 actinobacterial colonies were isolated by spread plate technique on Actinomycetes isolation agar, Kuster's agar and Starch casein agar. The isolate cultures were designated as UST1- UST8. Among them, UST3 showed a maximum zone of inhibition against clinical pathogens Salmonella typhi and Aspergillus niger with a zone of inhibition of 22mm and 20mm respectively. In solvent extraction study ethyl acetate and hexane was found as best solvents for extraction. Potential isolate UST3 was identified as Streptomyces variabilis using morphological studies and 16S rRNA sequencing. Potential strain was submitted as Streptomyces variabilis- VITUMVB03 Conclusion:Â Results obtained in this study concluded that marine actinobacteria have broad-spectrum antimicrobial activity and can be used in the pharmaceutical industry. Keywords: Anti-fungal activity, Anti-bacterial activity, Salmonella typhi, Aspergillus niger, Streptomyces variabilis